Epidemiology of injuries in National Collegiate Athletic Association women's basketball: 2014-2015 through 2018-2019 - Lempke, L. B.; Chandran, A.; Boltz, A. J.; Robison, H. J.; Collins, C. L.; Morris, S. N. (Journal of Athletic Training, 2021)
Context: Frequent inspection of sports-related injury epidemiology among National Collegiate Athletic Association (NCAA) women's basketball student-athletes is valuable for identifying injury-related patterns. Background: Emerging patterns in epidemiology of NCAA women's basketball injuries are unknown though general sports medicine practices, and playing rules and regulations have evolved in recent years. Methods: Athlete exposures (AEs) and injury incidence data were reported to the NCAA Injury Surveillance Program between 2014-2015 and 2018-2019. Injury counts, rates, and proportions were used to examine injury characteristics, and injury rate ratios (IRRs) were used to assess injury rate differences. Results: Practice and competition injury rates were 5.93 and 10.35 per 1000 AEs, respectively. Preseason injury rates were higher than regular (IRR = 1.41; 95% CI = 1.31, 1.53) and postseason (IRR = 3.12; 95% CI = 2.39, 4.07). Ankle sprains (14.3%), concussions (7.5%), and anterior cruciate ligament tears (2.5%) were the most commonly reported injuries. Summary: Higher rates of practice and competition injuries, as well as ankle sprains, were observed relative to previous reports; continuous monitoring is necessary to identify potential contributing factors to these trends.